2001
DOI: 10.1042/0264-6021:3530689
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol biosynthesis from lanosterol: molecular cloning, chromosomal localization, functional expression and liver-specific gene regulation of rat sterol Δ8-isomerase, a cholesterogenic enzyme with multiple functions

Abstract: Sterol Delta(8)-isomerase (SI) (EC 5.3.3.5), also known as emopamil binding protein or sigma receptor, catalyses the conversion of the 8-ene isomer into the 7-ene isomer in the cholesterol biosynthetic pathway in mammals. Recently, mutations of SI have been found to be associated with Conradi-Hünermann syndrome in humans. To investigate the in vitro and in vivo modes of molecular regulation of SI and its role in cholesterol biosynthesis in mammals, we isolated a full-length cDNA encoding rat SI. The deduced am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Although SI is an important enzyme possessing unique features in the cholesterol biosynthesis pathway, to date little is known about its regulation. A lone previous paper has addressed the sterol-mediated regulation of SI mRNA levels (18). Here we report that the SI gene promoter, like other SREBPresponsive genes, contains a cluster of essential responsive elements for SREBPs, Sp1 and NF-Y.…”
Section: Srebpsmentioning
confidence: 82%
“…Although SI is an important enzyme possessing unique features in the cholesterol biosynthesis pathway, to date little is known about its regulation. A lone previous paper has addressed the sterol-mediated regulation of SI mRNA levels (18). Here we report that the SI gene promoter, like other SREBPresponsive genes, contains a cluster of essential responsive elements for SREBPs, Sp1 and NF-Y.…”
Section: Srebpsmentioning
confidence: 82%
“…Examples of proteins whose activity is altered by cationic amphiphiles include G protein-coupled receptors, ion channels, membrane transporters, phospholipases, sphingomyelinase, sterol isomerases, and calmodulin (23)(24)(25)(26)(27)(28). Specificity is indicated by the finding that the activity of these proteins is altered by some cationic amphiphiles, but not by others.…”
Section: Discussionmentioning
confidence: 99%
“…SCAP appears to have a specific sensitivity to a subgroup of cationic amphiphiles, but this subgroup is not the same as the ones that affect other hydrophobic proteins. For example, the sterol C 8 -C 7 isomerase is inhibited by low concentrations of trifluoperazine, but it is also inhibited by similarly low concentrations of U18666A and ifenprodil, compounds that had minimal effect on SCAP conformation when added as high as 100 M (26,27). The sensitivity pattern of SCAP is perhaps closest to that of the soluble protein calmodulin, whose activity is inhibited by trifluoperazine ϭ chlorprothixene Ͼ chlorpromazine Ͼ clomipramine Ͼ haloperidol Ͼ promazine Ͼ imipramine Ͼ promethazine (24).…”
Section: Discussionmentioning
confidence: 99%
“…Both array analysis and real-time RT-PCR results indicated that vincolozin treatment significantly decreased the expression of Ebp and Idi, the protein products of both genes are involved in non-ratelimiting steps in cholesterol synthesis [44,45]. In human prostate cancer cells, androgen can induce the expression of lipogenic genes through the mediation of sterol regulatory element binding proteins (SREBPs) [46].…”
Section: Discussionmentioning
confidence: 98%